Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 1 - Introduction to Algebraic Expressions - Test: Chapter 1 - Page 78: 36



Work Step by Step

The given expression, $ 3[5(y-3)+9]-2(8y-1) $, simplifies to \begin{array}{l}\require{cancel} 3[5(y)+5(-3)+9]-2(8y)-2(-1) \\\\= 3[5y-15+9]-16y+2 \\\\= 3[5y]+3[-15]+3[9]-16y+2 \\\\= 15y-45+27-16y+2 \\\\= (15y-16y)+(-45+27+2) \\\\= -y+(-16) \\\\= -y-16 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.